Investigation of the Contribution of Entrepreneurial Behavior to Firm Growth using PLS-SEM Approach - Mayang Azkiah; Sonny Rustiadi (Eduvest - Journal of Universal Studies, 2026)
The bottled water industry in Indonesia has experienced significant growth driven by increasing health awareness and demand for safe drinking water. Despite this growth, the industry is characterized by low entry barriers, leading to intense competition, product homogeneity, and price sensitivity. As a result, many firms can enter the market easily but struggle to sustain long-term growth. This study addresses the challenge of achieving sustainable firm growth in such a competitive environment. This research integrates Entrepreneurial Orientation (EO), Entrepreneurial Leadership (EL), and Strategic Innovation (SI) as key determinants of firm growth. EO reflects a firm’s innovativeness, proactiveness, and risk-taking behavior, while EL ensures effective execution and organizational alignment. SI acts as a transformational mechanism that translates entrepreneurial intent into measurable performance outcomes. A quantitative, explanatory, and cross-sectional approach was employed, with data collected from bottled water SMEs in South Sulawesi. The analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine direct, mediating, and moderating relationships among variables. The findings indicate that EO alone is insufficient to drive sustainable growth without being supported by SI. SI plays a crucial mediating role in converting entrepreneurial behavior into operational efficiency and market differentiation. Furthermore, EL strengthens the relationship between EO and SI by enhancing execution capability and organizational readiness although the influence is not that strong. The interaction among these variables provides a more comprehensive explanation of firm growth than direct effects alone.